Trends in pulmonary exercise testing utilization after the COVID-19 pandemic in Ontario: A population-cohort study - Javier Silva-Valencia; Karen Tu; Rahim Moineddin; Debra A. Butt; Braden O’Neill; Anthony Train; Jessica Gronsbell; Andrea S. Gershon (PLoS ONE, 2026)
Introduction Pulmonary exercise testing, including six-minute walk tests, exercise oximetry, and independent exercise assessments, are critical tools for managing chronic respiratory and cardiac conditions, evaluating treatment response, and determining long-term oxygen therapy needs. During the COVID-19 pandemic, testing was reduced to limit viral spread. This study aimed to evaluate post-pandemic trends of pulmonary exercise testing utilization in Ontario overall and across demographic groups. Methods We conducted a population-based cohort study using Ontario administrative data between April 2015 and December 2023 to evaluate pulmonary exercise testing before, during, and after the COVID-19 pandemic. We used an Auto-Regressive Integrated Moving Average Model (ARIMA) model and incidence rate ratios to evaluate recovery trends. Subgroup analysis examined if trends were similar in different groups. Results During the study period, 505,902 tests were performed for 362,888 individuals. As of December 2023, testing rates were still 21% below pre-pandemic levels (IRR 0.79, 95%CI 0.70–0.89). Recovery was lower in males (IRR 0.76, 95%CI 0.66–0.86) and individuals living in lower socioeconomic status neighborhoods (IRR 0.71, 95%CI 0.58–0.86). Northern Ontario saw the most pronounced shortfall compared to other regions, with testing rates one-third of pre-pandemic levels (IRR 0.33, 95% CI 0.26–0.43). Conclusion More than three years after the pandemic began, pulmonary exercise testing rates have yet to return to pre-pandemic levels, with certain groups disproportionately affected. This highlights a significant and ongoing disruption in diagnostic capacity and quality of care for people with respiratory and cardiac diseases.